Geologi Kuarter dan Cuaca Daerah Lampung Barat, Kaitannya dengan Kejadian Longsor (Studi Kasus Jalur Jalan Transek Lampung Barat) - Iqbal, Prahara (Pusat Survei Geologi, 2018)
Deposition characteristic study in the West Lampung transect road based on field observation, soil mechanic analysis, and the weather of west Lampung study have been done to get its relationship to the landslide. The methods were used are geological mapping, laboratory analysis, and Lampung Barat weather data. Lampung Barat is an area with equatorial rainfall type, this type has ≥ 2000 mm of rainfall annually. The geological condition of Lampung Barat transects road illustrates that the area is predominantly composed by clay and sandy tuff that loose, unconsolidated, and high capacity expands characteristic. This condition caused the soil sediments of West Lampung transect road which form slope would be potentially to form landslides through intensely weightiness of rainwater.Keywords: Lampung Barat transect road, equatorial rainfall type, landslide.